The Drosophila DmGluRA is required for social interaction and memory - Schoenfeld, Brian P.; Choi, Richard J.; Choi, Catherine H.; Terlizzi, Allison M.; Hinchey, Paul; Kollaros, Maria; Ferrick, Neal J.; Koenigsberg, Eric H.; Ferreiro, David; Leibelt, David A.; Siegel, Steve J.; Bell, Aaron J.; et al. (Frontiers in Pharmacology, 2013)
Metabotropic glutamate receptors (mGluRs) have well established roles in cognition and social behavior in mammals. Whether or not these roles have been conserved throughout evolution from invertebrate species is less clear. Mammals have 8 mGluRs whereas Drosophila have a single DmGluRA, which has both Gi and Gq coupled signaling activity. We have utilized Drosophila to examine the role of DmGluRA in social behavior and various phases of memory. We have found that flies that are homozygous or heterozygous for loss of function mutations of DmGluRA have impaired social behavior in male Drosophila. Futhermore, flies that are homozygous or heterozygous for loss of function mutations of DmGluRA have impaired learning during training, immediate recall memory, short-term memory and long-term memory as young adults. This work demonstrates a role for metabotropic glutamate receptor activity in both social behavior and memory in Drosophila.